2013
DOI: 10.1177/0269216313511142
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency as a cause of chronic pain in the palliative medicine clinic: Two case reports

Abstract: The prevalence of vitamin D deficiency in the palliative care population merits further investigation, since these patients are at high risk of deficiency. Having an index of suspicion, particularly in those patients with known risk factors and pain that is not fully explained, may result in better pain control and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
1
11
0
4
Order By: Relevance
“…Without any doubt, avoiding falls and (spontaneous) fractures [8] even in palliative patient is meaningful. Vit D insufficiency creates secondary hyperparathyroidism with painful myopathy [9,10], muscle weakness, atrophy and acute arthritis due to chondrocalcinosis [11]. Quality of life is diminished, together with enhancing chronic pain [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without any doubt, avoiding falls and (spontaneous) fractures [8] even in palliative patient is meaningful. Vit D insufficiency creates secondary hyperparathyroidism with painful myopathy [9,10], muscle weakness, atrophy and acute arthritis due to chondrocalcinosis [11]. Quality of life is diminished, together with enhancing chronic pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…1 represents the supplementation ratios for each nursing home and at each measurement. We compared the baseline vitamin D supplementation ratio of the twelve first participating NH's [1][2][3][4][5][6][7][8][9][10][11][12], called ''naive NH's'', with the five other NH's [13][14][15][16][17] that involved later in the study, called ''knowing NH's'' because of the gathered knowledge about the first results. The ''knowing NH's'' had a significant higher supplementation ratio than the ''naive NH's'' (64.7% AE 19.0 versus 26.0% AE 12.8; P < 0.001), visually represented by the black lines on Fig.…”
Section: Supplementation Ratiosmentioning
confidence: 99%
“…Moreover, a recent case report indicated that patient suffering with abdominal pain due to cervical cancer-related treatment was improved after vitamin D replacement therapy [136].…”
Section: Vitamin D and Cervical Cancer Riskmentioning
confidence: 99%
“…21,22 A recent case series reported treatment with vitamin D in the palliative medicine clinic where patients with chronic cancer pain refractory to conventional therapy showed a favourable response. 23 Surgical incision releases inflammatory mediators that reduce the pain threshold at the injury site and in the surrounding uninjured tissue. The combination of vitamin D deficiency and surgical incision may thus be especially deleterious.…”
Section: Résumémentioning
confidence: 99%